2021
DOI: 10.3389/fcell.2021.803198
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Six-Gene SLC Family Signature With Prognostic Value in Patients With Lung Adenocarcinoma

Abstract: Given the importance of solute carrier (SLC) proteins in maintaining cellular metabolic homeostasis and that their dysregulation contributes to cancer progression, here we constructed a robust SLC family signature for lung adenocarcinoma (LUAD) patient stratification. Transcriptomic profiles and relevant clinical information of LUAD patients were downloaded from the TCGA and GEO databases. SLC family genes differentially expressed between LUAD tissues and adjacent normal tissues were identified using limma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…SLC2A1 is a glucose transport protein coding gene that controls the absorption of glucose, and the encoded protein is closely related to glucose metabolism. SLC2A1 is connected with tumor progression and metastasis [29] that upregulated with poorer prognosis, including in LUAD [30]. AURKA is a recognized tumor susceptibility gene, which is essential for the normal process of cell mitosis [31] and overexpressed in many cancers and consists of breast cancer [32], colorectal cancer [33], gastrointestinal cancer [34], bladder cancer [35], and lung cancer [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLC2A1 is a glucose transport protein coding gene that controls the absorption of glucose, and the encoded protein is closely related to glucose metabolism. SLC2A1 is connected with tumor progression and metastasis [29] that upregulated with poorer prognosis, including in LUAD [30]. AURKA is a recognized tumor susceptibility gene, which is essential for the normal process of cell mitosis [31] and overexpressed in many cancers and consists of breast cancer [32], colorectal cancer [33], gastrointestinal cancer [34], bladder cancer [35], and lung cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of SLC7A11-mediated cystine uptake results in intracellular glutathione deficiency, leading to ferroptosis-mediated cell death [7]. Xuan et al [30] reported that upregulated SLC7A11 was shown in NSCLC patients and is related to worse prognosis. ALOX5 is an initiation enzyme that mainly mediates the production of inflammatory mediators leukotriene and lipoxin.…”
Section: Discussionmentioning
confidence: 99%
“…A different study performed an in silico analysis on data derived from TCGA to study the association of SLC genes with lung adenocarcinoma. Low SLC26A11 expression was linked to worse overall survival [92]. However, according to the Human Protein Atlas, SLC26A11 gene expression is unfavorable in both liver and endometrial cancers [93].…”
Section: Discussionmentioning
confidence: 99%
“…Multi-omics analyses of SLCs in cancer have been crucial in detecting aberrant mechanisms leading to dysregulated transport rates (Figure 3c). Most commonly, the abnormal expression of SLCs beyond glucose transporters has been associated with the increased transport of metabolites and building blocks necessary for cancer development, which has been used to identify SLCs as prognostic biomarkers in pan-cancer [121,122] and cancerspecific studies [123][124][125]. In this context, ML has also helped further discriminate between the genes with the biggest effect within the cancer signatures [126].…”
Section: Solute Carriersmentioning
confidence: 99%